DEVELOPING STUDENTS' INFORMATION CULTURE IN INCLUSIVE EDUCATION (International Conference on Modern Science and Scientific Studies, 2025)
Modern educational technology refers to the use of ICT to effectively organize the educational process. Through these technologies it is possible to make education more interactive and interesting, to allow students to choose their own way of reading, and to increase the digital literacy of young people. Inclusive education is the provision of educational opportunities for all young people, including those with disabilities and those from socially vulnerable segments. This model promotes the development of young people as equal and active participants in society. The culture of information acquisition, on the other hand, is the ability of an individual to find, analyze, classify, and effectively use sources of information.